Rapid, sensitive, and highly specific detection of monkeypox virus by CRISPR-based diagnostic platform - Gong, Lin; Chen, Xiaomin; Wang, Yimei; Liang, Jiansheng; Liu, Xiaoli; Wang, Yi (Frontiers in Public Health, 2023)
Background Monkeypox (MPX), caused by the Monkeypox virus (MPXV), has incurred global attention since it broke out in many countries in recent times, which highlights the need for rapid and reliable diagnosis of MPXV infection. Methods We combined recombinase polymerase amplification (RPA) with CRISPR/Cas12a-based detection to devise a diagnostic test for detection of MPXV and differentiation of its two clades [Central Africa clade (MPXV-CA) and West Africa clade (MPXV-WA)], and called it MPXV-RCC. The sensitivity, specificity and practicability of this method have been analyzed. Results The optimal conditions of MPXV-RCC assay include two RPA reactions at 38°C for 25 min and a CRISPR/Cas12a-gRNA detection at 37°C for 10 min. The results of MPXV-RCC assay were indicated by a real-time fluorescence analysis software. Thus, the whole detection process, including rapid template preparation (20 min), RPA reaction (25 min) and CRISPR-based detection (10 min), could be finished within 1 hour. The sensitivity of MPXV-RCC for MPXV-CA and MPXV-WA detection was down to 5~10 copies of recombination plasmids and pseudovirus per reaction. Particularly, MPXV-RCC assay could clearly differentiate MPXV-CA from MPXV-WA, and had no cross-reactivity with other pathogens. In addition, the feasibility of MPXV-RCC assay was further validated by using spiked clinical samples. Conclusion The MPXV-RCC assay developed here is a promising tool for quick and reliable diagnosis of MPXV infection.